LAW ENFORCEMENT AGAINST TRANSACTION MODES INTERNATIONAL TRADE - Widya Romasindah Aidy; Alum Simbolon; Rr. Dijan Widijowati (Faculty of Law, Universitas Bhayangkara Jakarta Raya, 2024)
In the era of globalization, transnational crime is an inevitable trend as the lines between nations become more unified. One form of transnational crime that is very disturbing to various countries is money laundering which has several modes and one of them is international trade transactions. This mode is done through a Letter of Credit (L/C) document as a means. The purpose of this study is to determine the form of regulation against money laundering in the mode of international trade transactions and understand its law enforcement against the mode of international trade transactions. The type of research used is normative juridical research with a statutory approach to find out the overall legal regulations governing the examination of documents in L/C, and a conceptual approach using a way of looking at legal principles in legal theory. The result of this study is that the Government has regulated the use of L/C through Permendag Nomor 94 Tahun 2018, especially for exports of minerals, coal, oil and gas, and palm oil. This regulation requires the use of L/C from domestic banks for certain types of exports and imposes sanctions for violators of this regulation and its enforcement against abuse of the authority of credit facilities by banks through L/C, must immediately prioritize the improvement, improvement, and renewal of the Banking Law accompanied by firm law enforcement and managerial improvement of banking.